The Effect of Prenatal Alcohol Exposure on Fetal Growth and Cardiovascular Parameters in a Baboon Model of Pregnancy. (July 2018) - Tobiasz, Ana M.; Duncan, Jose R.; Bursac, Zoran; Sullivan, Ryan D.; Tate, Danielle L.; Dopico, Alex M.; Bukiya, Anna N.; Mari, Giancarlo
Prenatal alcohol exposure often results in an array of fetal developmental abnormalities termed fetal alcohol spectrum disorders (FASDs). Despite the high prevalence of FASDs, the pathophysiology of fetal damage by alcohol remains poorly understood. One of the major obstacles in studying fetal development in response to alcohol exposure is the inability to standardize the amount, pattern of alcohol consumption, and peak blood alcohol levels in pregnant mothers. In the present study, we used Doppler ultrasonography to assess fetal growth and cardiovascular parameters in response to alcohol exposure in pregnant baboons. Baboons were subjected to gastric alcohol infusion 3 times during the second trimester equivalent to human pregnancy, with maternal blood alcohol levels reaching 80 mg/dL within 30 to 60 minutes following alcohol infusion. The control group received a drink that was isocaloric to the alcohol-containing one. Doppler ultrasonography was used for longitudinal assessment of fetal biometric parameters and fetal cardiovascular indices. Fetal abdominal and head circumferences, but not femur length, were significantly decreased in alcohol-exposed fetuses near term. Peak systolic velocity of anterior and middle cerebral arteries decreased during episodes of alcohol intoxication, but there was no difference in Doppler indices between groups near term. Acute alcohol intoxication affected fetal cerebral blood flow independent of changes in the fetal cardiac output. Unlike fetal growth parameters, changes in vascular indices did not persist over gestation. In summary, alcohol effects on fetal growth and on fetal vascular function have different time courses.